Alterations in hippocampal subfield and amygdala subregion volumes in posttraumatic subjects with and without posttraumatic stress disorder. Issue 7 (10th February 2021) - Zhang, Lianqing; Lu, Lu; Bu, Xuan; Li, Hailong; Tang, Shi; Gao, Yingxue; Liang, Kaili; Zhang, Suming; Hu, Xinyue; Wang, Yanlin; Li, Lei; Hu, Xinyu; et al.
Abstract: The hippocampus and amygdala are important structures in the posttraumatic stress disorder (PTSD); however, the exact relationship between these structures and stress or PTSD remains unclear. Moreover, they consist of several functionally distinct subfields/subregions that may serve different roles in the neuropathophysiology of PTSD. Here we present a subregional profile of the hippocampus and amygdala in 145 survivors of a major earthquake and 56 non‐traumatized healthy controls (HCs). We found that the bilateral hippocampus and left amygdala were significantly smaller in survivors than in HCs, and there was no difference between survivors with ( n = 69) and without PTSD (trauma‐exposed controls [TCs], n = 76). Analyses revealed similar results in most subfields/subregions, except that the right hippocampal body (in a head‐body‐tail segmentation scheme), right presubiculum, and left amygdala medial nuclei (Me) were significantly larger in PTSD patients than in TCs but smaller than in HCs. Larger hippocampal body were associated with the time since trauma in PTSD patients. The volume of the right cortical nucleus (Co) was negatively correlated with the severity of symptoms in the PTSD group but positively correlated with the same measurement in the TC group. This correlation between symptom severity and Co volume was significantly different between the PTSD and TCs. Together, we demonstrated that generalized smaller volumes in the hippocampus and amygdala were more likely to be trauma‐related than PTSD‐specific, and their subfields/subregions were distinctively affected. Notably, larger left Me, right hippocampal body and presubiculum were PTSD‐specific; these could be preexisting factors for PTSD or reflect rapid posttraumatic reshaping. Abstract : The current study presented a subregional profile of the hippocampus and amygdala in 145 survivors of a major earthquake and 56 nontraumatized healthy controls (HCs). They found that generalized smaller volumes in the hippocampus and amygdala were more likely to be trauma‐related than PTSD‐specific, and their subfields/subregions were distinctively affected. A larger left medial nuclei of the hippocampus, right hippocampal body, and presubiculum were found to be PTSD‐specific.